The Experience of Pregnant Women in the Health Management Model of Internet-Based Centering Pregnancy: A Qualitative Study - Dai J; Yu Y; Wang Y; Huang Y; Liu J; Lin Y; Fan X; Zhang M; Xu X; Bai J; Chen H; Liu Y (Dove Medical Press, 2022)
Jiamiao Dai,1,* Yun Yu,2,* Yuchen Wang,3 Yinying Huang,4 Juan Liu,5 Yumin Lin,4 Xiaoxiao Fan,1 Mingjing Zhang,4 Xiaofang Xu,4 Jinbing Bai,6 Hong Chen,2,* Yanqun Liu1,* 1School of Nursing, Wuhan University, Wuhan, People's Republic of China; 2Department of Nursing, Zhongnan Hospital of Wuhan University, Wuhan, People's Republic of China; 3Department of Nursing, Taiyuan Central Hospital of Shanxi Medical University, Taiyuan, People's Republic of China; 4Department of Nursing, Women and Children's Hospital, School of Medicine, Xiamen University, Xiamen, People's Republic of China; 5Department of Gynaecology and Obstetrics, Zhongnan Hospital of Wuhan University, Wuhan, People's Republic of China; 6Nell Hodgson Woodruff School of Nursing, Emory University, Atlanta, GA, USA*These authors contributed equally to this workCorrespondence: Yanqun Liu, School of Nursing, Wuhan University, Wuhan, People's Republic of China, Tel +86 27-68758591, Email liuyanqun1984@163.com Hong Chen, Department of Nursing, Zhongnan Hospital of Wuhan University, Wuhan, People's Republic of China, Tel +86 27-68758591, Email 2077374407@qq.comBackground: CenteringPregnancy Care is a promising group prenatal care innovation that combines assessment, education, and peer support. In China, it is not clear how best to integrate the CenteringPregnancy Care into existing maternal health care models. This qualitative study aimed to explore Chinese pregnant women's experience in the Internet-based CenteringPregnancy management model.Methods: The Internet-based CenteringPregnancy was applied in a tertiary hospital between 2018 and 2019 in Wuhan, Hubei Province. Through purposive sampling, a total of 9 pregnant women who had experienced Internet-based CenteringPregnancy were recruited. A semi-structured interview was used to collect qualitative data, and Colaizzi's 7-step method of phenomenological data analysis was used to analyze the collected data.Results: Three themes were extracted from the participants' interviews, including: 1) empowerment; 2) psychological and social support; 3) challenges of the Internet-based CenteringPregnancy. The Internet-based CenteringPregnancy management model retained advantages of CenteringPregnancy, emphasizing the pregnant woman as the subject of health care and promoting them to participate in health care. Participants believed that they could exchange pregnancy knowledge, help each other, and improve mood both timely and efficiently from the new model. However, it was found that there were challenges in seminar time arrangement, topic selection, and discussion management.Conclusion: The Internet-based CenteringPregnancy management model positively affected pregnant women's empowerment, psychological, and social support. It is recommended to improve the seminar's design in future studies.Keywords: CenteringPregnancy, mobile health, health management, prenatal care